Anion Constructor for Atomic‐Scale Engineering of Antiperovskite Crystals for Electrochemical Reactions. (29th January 2021) - Lee, Sehyun; Jung, Jae Young; Jang, Injoon; Choi, Daeil; Lee, Myeong Jae; Lee, Dong Wook; Jang, Jue‐Hyuk; Lee, Jeong Hee; Jin, Haneul; Im, Kyungmin; Lee, Eungjun; Kim, Seung‐hoon; et al.
Abstract: Among the Pt group metals, Pd has been considered the most efficient for application in electrocatalysts as an alternative to Pt. Despite the comparable electrochemical activities of Pd and Pd‐metal alloys, they are vulnerable to liquid acidic electrolytes, leading to degradation of catalytic activity. Pd–Ni alloys have been used to enhance catalytic activity because the electronic structure of Pd can be easily changed by adding Ni. In other studies, N atoms have been introduced for more stable M–Ni catalysts by inducing the formation of Ni4 N species; however, the structural analysis and the role of nitrogen have not been fully understood yet. Herein, the Pd–Ni alloy nitride with a unique crystal structure shows a promising catalytic activity for oxygen reduction reaction (ORR). The nitride PdNi nanoparticles have a novel monolithic antiperovskite structure of chemical formula (Pd x Ni1− x )NNi3 . The unique antiperovskite crystal (Pd x Ni1− x )NNi3 possesses superior ORR activity and stability, originating from the downshifted d‐band center of the monolayer Pd/antiperovskite surface and the lower formation energy of the antiperovskite core nanocrystal. Consequently, (Pd x Ni1− x )NNi3, as a Pt‐free Pd‐based electrocatalyst, overcomes the stability issue of Pd under acidic conditions by achieving 99‐times higher mass activity than commercial Pd/C, as shown by the durability test. Abstract : Monolithic antiperovskite crystals are synthesized through atomic‐scale engineering. Then nitride PdNi alloy achieves excellent catalytic activity and durability under acidic media, resulting from the synergistic effect of nitride and intermetallic structures. This strategy will pave the way for overcoming the catalytic performance of potential materials.